2020
DOI: 10.34172/apb.2021.029
|View full text |Cite
|
Sign up to set email alerts
|

Roles of miRNAs in Colorectal Cancer: Therapeutic Implications and Clinical Opportunities

Abstract: As many investigations have reported, there is a complicated relation between fermented foods, lactic acid bacteria (LAB), and human health. It seems that bioactive components such as prebiotics, probiotics, and postbiotics are key mediators of the complex and direct association between these factors. LAB activity in the matrix of fermented foods and improving their growth by prebiotic compounds ultimately results in the production of bioactive molecules (postbiotics), which possess specific biological and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 148 publications
0
11
0
Order By: Relevance
“…Several studies reported alterations of miRNA profile in CRC, including miR-186-5p, miR-22-3p, miR-22-5p, miR-25-3p, miR-92a-3p, and miR-16-5p, compared with healthy subjects. 30 , 31 Upregulated miRNAs can target the downregulation of different tumor suppressor genes involved in CRC development, while in the healthy tissues miRNA silencing can attenuate the activity of proto-oncogenes. 30 Indeed, the CRC carcinogenesis is finely regulated by miRNA content, particularly in the adenoma-carcinoma transition.…”
Section: Mirnas: Emerging Targets For Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported alterations of miRNA profile in CRC, including miR-186-5p, miR-22-3p, miR-22-5p, miR-25-3p, miR-92a-3p, and miR-16-5p, compared with healthy subjects. 30 , 31 Upregulated miRNAs can target the downregulation of different tumor suppressor genes involved in CRC development, while in the healthy tissues miRNA silencing can attenuate the activity of proto-oncogenes. 30 Indeed, the CRC carcinogenesis is finely regulated by miRNA content, particularly in the adenoma-carcinoma transition.…”
Section: Mirnas: Emerging Targets For Cancer Treatmentmentioning
confidence: 99%
“… 30 , 31 Upregulated miRNAs can target the downregulation of different tumor suppressor genes involved in CRC development, while in the healthy tissues miRNA silencing can attenuate the activity of proto-oncogenes. 30 Indeed, the CRC carcinogenesis is finely regulated by miRNA content, particularly in the adenoma-carcinoma transition. Increased miR-135a/b expression is associated with decreased APC levels and Wnt signaling pathway activation, pivotal features of the transformation from normal colonic epithelium into adenoma.…”
Section: Mirnas: Emerging Targets For Cancer Treatmentmentioning
confidence: 99%
“…Angiogenesis is a process which forms new vasculature and is induced by vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), platelet-derived growth factor (PDGF), basic fibroblast growth factor (bFGF), transforming growth factor β (TGF-β), tumor necrosis factor α (TNF-α) and interleukin-8 (IL-8) and these factors can be carried by TDEs [ 12 ]. Besides, some exosomal-derived miRNAs have been detected that play a role in regulating angiogenic transcription factors, promoting angiogenesis and MDR in CRC [ 4 ]. Studies on rich-nutrition wheatgrass juice (WGJ) that extracted from plant Triticum aestivum, revealed post-chemotherapy improvement and modifying tumor associated microvesicles including exosomes properties by daily consumption of WGJ in CRC patient undergoing chemotherapy [ 29 ].…”
Section: Drug Resistance Mechanisms In Crcmentioning
confidence: 99%
“…Traditional cancer therapy including surgery, radiation, cryosurgery and chemotherapy are prone to exhibit undesired side effects and toxicity for patients [ 3 ]. Multiple drug resistance (MDR) can be considered as an obstacle for controlling disease and inhibition of tumors [ 4 ]. Different factors cause MDR like overexpression of ABC transporter especially P-gp, mutations [ 5 ], DNA damage and resistance to former chemotherapy drug due to clonal evolution, tumor heterogeneity [ 6 ], presence of cancer stem cell-like cells [ 7 ], dormancy [ 8 ], hypoxia [ 9 ], immune evasion [ 10 ], horizontally gene/material transfer [ 11 ], and tumor microenvironment complexity [ 12 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRNAs) have been described to play a significant role in cancer [ 10 ]. Numerous reports of altered miRNA expression have been linked to various pathologies [ 11 , 12 , 13 ], including BC [ 14 , 15 ]. MiRNAs are small non-coding RNAs that regulate gene expression in key biological processes such as proliferation, apoptosis, invasion, and metastasis [ 16 , 17 , 18 ] and have recently emerged as regulators of the complex mechanisms that drive BC therapeutic resistance or sensitivity.…”
Section: Introductionmentioning
confidence: 99%